MCQs in Radiology : with answers and exolanations - Bhargava, Satish K. (Jaypee Brothers Medical Publishers, 2011)
The overwhelming response and the input from the rreaders alobg with new development in the field of radiology and imaging has prompted us to add more questions soas to keep pace with the technological advancements.. The book will definitely be useful to improve the general understanding of the subject and also to provide an in depth knowledge of radiology and imaging not just to clear variousPG Entrance Exams but also to become better clinicians.